Depcition of Brahma on the Bhadra of the Garbhagriha - Temples of India Project Team (Jio Institute, 2024)
The bhadra (central offset) on the rear wall of the garbhagriha (sanctum sanctorum) is installed with the figure of Brahma. Despite significant damage, the deity is depicted seated on a pedestal, with three faces and four arms. While his upper arms are broken, he holds a kamandalu (water pot) in his lower left hand and makes a varada hasta (boon-giving gesture) with his lower right hand. He is adorned with a jatamukuta (crown of matted hair), a moustache, and a beard.